Measurement and evolution of eco-efficiency of coal industry ecosystem in China. (1st February 2019) - Wang, Delu; Wan, Kaidi; Yang, Jingyuan
Abstract: China's energy consumption and environmental problems are becoming increasingly urgent issues, with the ongoing rapid development of the nation's economy. A further investigation of eco-efficiency of the coal industry ecosystem (CIE) would contribute toward the healthy development of coal-mining cities. This study uses the stochastic frontier analysis (SFA) based on the assumptions of the Translog production function to assess the eco-efficiency of CIE and the potential promotion of 28 typical coal-mining cities in China. The results show that although the eco-efficiency of CIE of coal-mining cities is not high, it witnessed an overall increase from 2007 to 2014. In regional terms, coal-mining cities in the east have the highest eco-efficiency, while coal-mining cities in the west have the highest potential promotion; additionally, coal-mining cities in the northeast have the lowest eco-efficiency and potential promotion. Overall, the regional differences are significant. Moreover, the ownership structure and environmental regulations have significant inhibitory effects on the improvement of eco-efficiency, while marketization level, technological innovation, and energy price have significantly positive impacts. Graphical abstract: Image 1 Highlights: Evaluation model of eco-efficiency of coal industry ecosystem is established. Regional differences in eco-efficiency and potential promotion are illuminated. Evolution laws of eco-efficiency and potential promotion are explored. Influence factors of eco-efficiency of coal industry ecosystem are discussed.